Preparation and Characterization of Cattail Cellulose Films as Environmentally Friendly for Drug-Controlled Release System - SRIHANAM, P.; KHAMKON, S. (Asian Journal of Chemistry, 2023)
The objective of this work was to extract cellulose from cattail plants by treatment with 10 % (w/v) sodium hydroxide for 3 h at 80 ºC and bleached with 2% (v/v) sodium hypochlorite for 1 h. The sample was cut with 1% (v/v) sulfuric acid for 1 h to obtain 27.88% cellulose. The extracted cellulose was then prepared as films by casting method in a petri dish. The cellulose films were light brown and transparent with random direction of an orientation. The cellulose film increased transparency and flexibility by adding glycerol. The FTIR results clearly revealed the cellulose functional groups and some peaks being shifted when mixed glycerol. The cellulose films have a maximum decomposition temperature (Td,max) of 310-340 ºC and the decomposition temperature decreases slightly when mixed with glycerol. Mixing methylene blue, a sample hydrophilic drug, the cellulose films have increased their texture brittle and found micro-porous on surfaces. In addition, the differences in peaks of the cellulose functional groups were also observed. These might be caused by the interaction formation of methylene blue functional groups and cellulose. The interaction resulted in an increase in the Td,max of the films. The release of the methylene blue pattern concerned the amount of mixed methylene blue. These results can be used as a basis for extracting cellulose from cattail plants and preparing cellulose films for specific applications such as drug-controlled release system.